TPU-based elctrospun nanofibers assembled with nonwoven structure for face mask’s application - Hebie, Ali; Moretti, Joséphine; Mohsenzadeh, Elham; Gidik, Hayriye; Lewandowski, Maryline; Vroman, Philippe (Wydawnictwo Politechniki Łódzkiej, 2022)
The outbreak of Coronavirus Disease 2019 (COVID-19) has triggered great global public health concerns. Face masks are essential tools to reduce the spread of SARS-CoV-2 from human to human. However, there are still challenges with extending the serving life and maintaining the filtration performance of the current commercial masks. Filters composed of ultrafine fibers with diameters down to tens of nanometers have the potential to physically block viruses. The idea of developing an electrospun membrane with these ultrafine fibers to be integrated into the mask seems an innovative idea. A right mechanism must be developed to make it happen. This study presents the development of an electrospun membrane on a non-woven support by using thermoplastic polyurethane (TPU) for face masks.
Keywords: electrospinning; face mask; thermoplastic polyurethane (TPU); nanofibers; filtration; elektroprzędzenie; maska ​​na twarz; termoplastyczny poliuretan (TPU); nanowłókna; filtracja